Preliminary screening of cardamom (Elettaria cardamomum Maton) elite clones for thrips (Sciothrips cardamomi Ramk.) damage in the field - CHANDRAPPA, C PARVATHI, H M (Journal of Spices and Aromatic Crops, 1993)
Seventy three elite cardamom (Elettaria cardamomum) clones were screened for tolerance to thrips (Sciothrips cardamomi) damage under natural infestation. Three colones, viz., D-514, D-769 and CI-754 were promising with least damage to capsules.